The Influence of Social Media Use on Students’ Learning Patterns in Senior High Schools in West Sumatra - Dina Dahliana; Ana Hakimah Binti Saufi; Muthi'ah; Silfi Melindawati; Akmal Yandi; Naufal Narawangsa (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2025)
This study explores the diverse impacts of social media use on educational processes and outcomes. It aims to understand how social media platforms influence students' academic performance, engagement, and interpersonal skills. The population of this research was high school/vocational school students in West Sumatra with a research sample of one hundred and eighty three students. The data collection technique used is a questionnaire (survey) which consists of multiple choices and essays. Using a mixed methods approach, this research combines quantitative data from surveys distributed to respondents as well as qualitative insights gathered from in-depth interviews with educators and students. Findings suggest that social media can serve as a powerful educational tool when used effectively, increasing collaboration, access to information, and student motivation. However, this also presents challenges such as distractions, misinformation, and potential negative impacts on students' mental health. This study underscores the need for strategic integration of social media into educational frameworks to maximize its benefits while mitigating its drawbacks. Recommendations for educators include incorporating social media literacy into the curriculum, establishing clear guidelines for its use, and encouraging balanced digital consumption among students.